Optimal placement and sizing of DG in distribution system using accelerated PSO for power loss minimization - Mahesh, K. (Institute of Electrical and Electronics Engineers Inc., 2015)
Electrical power distribution system is typically radial in nature, consists of huge number of branches and nodes which eventually increases the power losses and decrease voltage profile of the system. Distributed generation (DG) in distribution system not only plunges the power losses but also it improves the system voltage quality. Optimal placement and sizing of DG in distribution system is still a challenging problem for exploiting the maximum benefits from it. In this paper a new method called as accelerated particle swarm optimization (APSO) is employed to minimize the total power loss of the system. The technique satisfies the power balance, bus voltage and system capacity as constraints. The method is tested for two different types of DG on standard IEEE 33 bus radial distribution system. The proposed method is found to be very effective for power loss reduction with fast convergence. Â© 2015 IEEE.